2011
DOI: 10.1097/mpg.0b013e318216940e
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and Intraobserver Agreement in 24‐hour Combined Multiple Intraluminal Impedance and pH Measurement in Children

Abstract: Most measurements showed substantial to perfect intra- and interobserver agreement. Still, we found a few outliers presumably caused by poorer signal quality in some tracings rather than being observer dependent. An improvement of analysis results may be achieved by using a standard analysis protocol, a standardized method for judging tracing quality, better training options for method users, and more interaction between investigators from different institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…It is not easy to compare previous reports with ours because those studies considered all reflux episodes together, i.e., without separating acid and non-acid reflux, and data were presented in different formats. Regarding inter-observer agreement, the 2 observers in the study by Pilic et al 9 had an agreement which varied widely among the 24 tracings, from 0 to 98% with a median of 73%, whereas the 2 observers in the study by Zerbib et al 11 had an overall agreement of 84% off PPIs and 73% on PPIs. Our results, obtained analyzing 40 tracings, showed lower inter-observer agreement on number of non-acid compared to acid reflux episodes (48.9-81.5% vs. 86.3-97.6%).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is not easy to compare previous reports with ours because those studies considered all reflux episodes together, i.e., without separating acid and non-acid reflux, and data were presented in different formats. Regarding inter-observer agreement, the 2 observers in the study by Pilic et al 9 had an agreement which varied widely among the 24 tracings, from 0 to 98% with a median of 73%, whereas the 2 observers in the study by Zerbib et al 11 had an overall agreement of 84% off PPIs and 73% on PPIs. Our results, obtained analyzing 40 tracings, showed lower inter-observer agreement on number of non-acid compared to acid reflux episodes (48.9-81.5% vs. 86.3-97.6%).…”
Section: Discussionmentioning
confidence: 92%
“…17 Our study investigated also intra-and inter-observer agreements on number of acid and non-acid reflux episodes. Previous studies have addressed this topic in the paediatric 8,9 and in the adult healthy 11 and GERD population, 10 although the 2 latter studies looked at inter-observer agreement only. Furthermore in the paper by Ravi et al 10 analysis was limited to classifying trac-ings with either normal or pathological number of reflux episodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from previous MII-pH studies has demonstrated that non-acid reflux accounts for at least half of reflux episodes, and bears a strong correlation with symptoms. The capabilities of MII-pH testing have been recognized, with many studies comparing the results with pH monitoring exclusively, especially for evaluation of the temporal connection between GER and symptoms [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Eine automatisierte Auswertung ist sensitiv, jedoch nicht spezifisch, sodass eine manuelle Kontrolle nach entsprechender Einarbeitung erforderlich ist. Dieser Aspekt wurde bei aktuellen Untersuchungen untermauert [308,309]. Normative Werten wurden anhand von Untersuchungen an gesunden Probanden ermittelt [310].…”
Section: Auswertungunclassified